Electromagnetic wave absorption properties based on slot size of biomass hollow pyramidal microwave absorber / Mas Izzati Fazin … [et al.] - Fazin, Mas Izzati; Razali, Ahmad Rashidy; Abdullah@Idris, Hasnain; Taib, Mohd Nasir; Mohamad Noor, Norhayati; Mohamat Kasim, Nazirah; Ahmad, Azizah; Mohd Kasim, Linda; Ismail, Noor Azila (Universiti Teknologi MARA, 2021)
Pyramidal microwave absorbers are used in an echoic chambers to eliminate unwanted signal wave that downgrade the quality of electromagnetic wave radiation measurement operation. Microwave absorbers are necessary to eliminate radiation wave reflection and to reduce signal leakage from various electronic equipments. Unfortunately, common material used in commercial absorbers are often expensive, non-modifiable and non-biodegradable. To address the problem and hence to achieve optimal electromagnetic wave absorption performance, new investigation into designs of different rectangular slot size on biomass absorber is presented in this paper. Three rectangular slot sizes are considered in the investigation to vary the electromagnetic wave absorption performance. These small, medium and big rectangular slot size are designed on hollow pyramidal microwave absorber are observed to analyzed their absorption performance at the frequency band of L, S, C and X-band. The proposed slotted pyramidal microwave absorber designs are measured using NRL arch free space measurement technique to determine its absorption performance at the frequency bands. Results comparison shows that small slot size posses the highest absorption performance at all frequency bands followed by medium and big slot size. The result indicates that small slot size is a good candidate to improve pyramidal microwave absorber performance.